2016
DOI: 10.11138/mltj/2016.6.3.384
|View full text |Cite
|
Sign up to set email alerts
|

Deep gluteal space problems: piriformis syndrome, ischiofemoral impingement and sciatic nerve release

Abstract: SummaryBackground: Deep gluteal syndrome (DGS) is an underdiagnosed entity characterized by pain and/or dysesthesias in the buttock area, hip or posterior thigh and/or radicular pain due to a non-discogenic sciatic nerve entrapment in the subgluteal space. Multiple pathologies have been incorporated in this all-included "piriformis syndrome", a term that has nothing to do with the presence of fibrous bands, obturator internus/ gemellus syndrome, quadratus femoris/ischiofemoral pathology, hamstring conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…The sciatic nerve has attachment systems that keep anatomical relationships stable in the buttocks [20]. These support mechanisms are formed by collateral branches of the sciatic nerve (the most well-known are superior gluteal nerve, inferior gluteal nerve, posterior skin nerve of the thigh) [1]; but also by the nerves and vessels of the pyramidal, gemellus, obturator internus and quadratus femoris muscles (superior and inferior gluteal arteries with terminal ischial branch). These attachment systems are associated with the paraneural connective tissue, which acts as a Bgliding system^with adjacent tissues or muscles (with its corresponding perimysium).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sciatic nerve has attachment systems that keep anatomical relationships stable in the buttocks [20]. These support mechanisms are formed by collateral branches of the sciatic nerve (the most well-known are superior gluteal nerve, inferior gluteal nerve, posterior skin nerve of the thigh) [1]; but also by the nerves and vessels of the pyramidal, gemellus, obturator internus and quadratus femoris muscles (superior and inferior gluteal arteries with terminal ischial branch). These attachment systems are associated with the paraneural connective tissue, which acts as a Bgliding system^with adjacent tissues or muscles (with its corresponding perimysium).…”
Section: Discussionmentioning
confidence: 99%
“…In the gluteal space, the sciatic nerve is protected from the sacrum by the pyramidal muscle, and later from the ischium by the gemellus muscles (superior and inferior), the obturator internus, and, finally, the quadratus femoris muscle. This deep pathway to the gluteus maximus is mainly characterized by the nerve's curved layout until reaching the second part of the route, at the level of the thigh [1,2]. Upon reaching the thigh, the sciatic nerve takes on a rectilinear route, deep into the long section of the biceps femoris.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long duration of sitting might be as a predisposing factor for piriformis syndrome, supported by the study of Carro et al and Mondal et al (2017). 4,11 However, both studies did not correctly state the duration of sitting a day which could be considered as a predisposing factor. Park et al concluded that inactive populations who sit more frequently for long periods (duration ≥8 hours) have a tendency to experience lower back pain than other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Upon surgical exploration of the sciatic nerve, a fibrotic tendinous scar beneath the piriformis was found and released. The resection was done from trochanter's attachment, by separating joint tendon from m. piriformis and m. obturator internus, and by releasing n. peroneus and n. tibialis from fibrous bands and surrounding muscles [15][16][17][18] (Fig 4).…”
Section: Discussionmentioning
confidence: 99%